“Anemia en adolescentes gestantes y su repercusión materna en usuarias del Centro De Salud 10 De Noviembre Del Cantón Ventanas, octubre 2018 – abril 2019” - Solano Meza, Evelin Jeomar (2019)
A non - experimental, cross - sectional study was designed using methods of observation and analysis of the clinical records of the adolescents treated at the health center on November 10, which allowed to establish the repercussions of anemia in the adolescent pregnancy in female users. health center November 10, Cantón Ventanas. A study population of 300 adolescents was used, an intentional sampling technique was applied, which allowed selecting pregnant adolescents with anemia, which represented 70 cases, obtaining the following results: the incidence of anemia in adolescent pregnancy was 23%, the repercussions represented in more frequent maternal complications were urinary tract infections 53%, arterial hypertension 7%, abortion 11%, threat of abortion 24%, 1 case of Oligohydramnios and 1 case of Polyhydramnios.